2006
DOI: 10.1007/s00392-006-0373-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased cardiac mRNA expression of matrix metalloproteinase-1 (MMP–1) and its inhibitor (TIMP–1) in DCM patients

Abstract: Left ventricular dilation and myocardial remodeling are hallmarks of dilated cardiomyopathy (DCM). It is assumed that left ventricular dilation is caused by the disintegration of the collagenous network by increased collagenolytic activity of matrix metalloproteinases (MMPs) and their adequate tissue inhibitors (TIMPs). In this study the myocardial MMP-1 and TIMP-1 mRNA expressions were investigated by using real-time quantitative PCR analysis from right septal endomyocardial biopsies of patients with dilated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Felkin et al 25 Published reports on TIMP levels in DCM diverge. Decreasing 26,27 as well as increasing 14,23 levels are reported, yet again, the earlier studies tended to look at end-stage disease, whereas the latter observed earlier stages. Furthermore, mRNA levels in our study diverged to a high degree among the pigs.…”
Section: Discussionmentioning
confidence: 95%
“…Felkin et al 25 Published reports on TIMP levels in DCM diverge. Decreasing 26,27 as well as increasing 14,23 levels are reported, yet again, the earlier studies tended to look at end-stage disease, whereas the latter observed earlier stages. Furthermore, mRNA levels in our study diverged to a high degree among the pigs.…”
Section: Discussionmentioning
confidence: 95%
“…Further, upregulation of different matrix metalloproteases (MMPs 1, 2 and 9) has been reported in both short and long term settings of Dox treatment in animal and cell culture models [7], [59][61]. In the absence of sufficient quantities of tissue inhibitors of metalloproteases (TIMPs), activated MMPs can digest collagen matrix and ECM and trigger reparative fibrosis in Dox induced or dilated cardiomyopathy [59], [61], [62]. Although we have not measured MMP levels in our study, differences in the time course of MMP activation may also account for the early onset of fibrosis observed in our study compared to the absence of fibrosis in the acute setting of an earlier study [58].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with end-stage dilated cardiomyopathy, analysis of LV myocardial tissue showed decreased MMP1, increased MMP3, MMP9, TIMP1 and TIMP2, and no changes in MMP2 levels [106]. Picard and colleagues reported increased MMP1 and TIMP1 mRNA levels in right septal endomyocardial biopsies from patients with dilated cardiomyopathy that did not correlate with LV diameter, whereas collagen volume density correlated well with LV diameter in these patients [107]. Hypertensive patients with cardiac hypertrophy have been reported to have reduced plasma levels of MMP1 [97], MMP2 and MMP9 [108], while elevated plasma TIMP1 levels have been reported in hypertensive patients [97] that correlated with diastolic dysfunction and LV fibrosis [98].…”
Section: Reviewmentioning
confidence: 99%